2011
DOI: 10.3109/0886022x.2011.615969
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a Population at Risk of Chronic Kidney Disease: Analysis of Factors Associated with Low eGFR and Microalbuminuria

Abstract: Background and objective: Numerous screenings of chronic kidney disease (CKD) have been performed all over the world. This screening study was undertaken with the aim of estimating the prevalence of low glomerular filtration rate (eGFR) and microalbuminuria (MAU) and/or proteinuria in a population at risk for CKD and to detect factors associated with these CKD markers. Materials and methods: This cross-sectional study included 1617 patients without previously known kidney disease who came for regular check-ups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
2
6
1
Order By: Relevance
“…In agreement with the results of this study, a number of studies have reported that cigarette smoking is associated with higher eGFR [22][24], while others have found the reverse [25], [41].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the results of this study, a number of studies have reported that cigarette smoking is associated with higher eGFR [22][24], while others have found the reverse [25], [41].…”
Section: Discussionsupporting
confidence: 92%
“…Research into the associations between later life influences and kidney function have shown conflicting results for body mass index (BMI) [16][20] and smoking [21][25], and a positive association for current SES [26][28]. The Newcastle Thousand Families birth cohort [29][30] provided a unique opportunity to analyse longitudinal data and investigate the effects of both early and later life influences on kidney function at age 63–64 years.…”
Section: Introductionmentioning
confidence: 99%
“…While the bias introduced is negligible in many patients it cannot be ruled out that some where misclassified. It was recently shown however, that dipstick screening of microalbuminuria could be used in a population at risk of chronic kidney disease [35]. 5) We obtained no information on blood glucose or HbA1c.…”
Section: Discussionmentioning
confidence: 94%
“…The most effective method is apparently to evaluate various clinical factors such as those suggested by the Kidney Heath Check: blood pressure, eGFR and urinalysis [7]. Other studies combine eGFR evaluation with microalbuminuria and/or proteinuria [11,12,13,14]. However, there is some debate whether these full tests are economically viable on a large scale [7,9,15].…”
Section: Discussionmentioning
confidence: 99%